Perancangan Buku Ilustrasi Asal Usul Suku Batak di Tanah Sumatera Utara - ; Muhammad Adiba Naufal (Syntax Idea)
Batak tribe is one of the largest ethnic groups in Indonesia, this tribe is spread almost throughout the province of North Sumatra. This tribe is famous for its family or surname side, and the language used by sub-tribes is also different, for example Batak Toba language is different from Batak karo. Although this batak tribe is known for its characteristics, not everyone knows or rarely knows where the origin of the batak tribe itself, especially the younger generation. This design aims to provide information about the origin of the batak tribe in the form of illustration book media, with this design the author makes the design interesting and easy to understand. The method used in the design of this illustrated book is the Collection of Data from Books, Articles and the Internet. The final result of this design is expected that the younger generation knows the origin of the Batak tribe, with the creation of this Illustration Book the younger generation will understand the origin of the Batak tribe itself.